Does the Identification of a Minimum Number of Cases Correlate With Better Adherence to International Guidelines Regarding the Treatment of Penile Cancer? Survey Results of the European PROspective Penile Cancer Study (E-PROPS) - Lebentrau, Steffen; Wakileh, Gamal Anton; Schostak, Martin; Schmid, Hans-Peter; Suarez-Ibarrola, Rodrigo; Merseburger, Axel S.; Hutterer, Georg C.; Necknig, Ulrike H.; Rink, Michael; Bögemann, Martin; Kluth, Luis Alex; Pycha, Armin; et al. (Frontiers in Oncology, 2021)
Background Penile cancer (PC) represents a rare malignant disease, whereby a small caseload is associated with the risk of inadequate treatment expertise. Thus, we hypothesised that strict guideline adherence (GA) might be considered a potential surrogate for treatment quality. This study investigated the influence of the annual hospital caseload on GA regarding treatment recommendations for PC. Methods In a 2018 survey study, 681 urologists from 45 hospitals in 4 European countries were queried about 6 hypothetical case scenarios (CS): local treatment of the primary tumour pTis (CS1), pT1b (CS2); lymph node surgery inguinal (CS3), pelvic (CS4); chemotherapy neoadjuvant (CS5), adjuvant (CS6). Only the responses from 206 head and senior physicians, as decision makers, were evaluated. The answers were assessed based on the applicable EAU guidelines regarding their correctness. The real hospital PC-caseload was analysed based on multivariate logistic regression models regarding its effect on GA. Results The median annual hospital PC-caseload was 6 (IQR 3-9). Recommendations for CS1-6 were correct in 79%, 66%, 39%, 27%, 28% and 28%, respectively. The probability of a GA recommendation increased with each PC-patient treated per year in a clinic for CS1, CS2, CS3 and CS6 by 16%, 7.8%, 7.2% and 9.5%, respectively (each p<0.05); CS4 and CS5 were not influenced by PC-caseload. A caseload threshold with a higher GA for all endpoints could not be perceived. The type of hospital care (academic vs. non-academic) did not affect GA in any scenario. Conclusions GA for most treatment recommendations increases with growing annual PC-caseload. Thus, the results of our study call for a stronger centralisation of diagnosis and treatment strategies regarding PC.